The Kazakh khanates between the Russian and Qing empires - Noda, Jin.
1 online resource.
Keywords: In The Kazakh Khanates between the Russian and Qing Empires , Jin Noda examines the foreign relations of the Kazakh Chinggisid sultans and the Russian and Qing empires during the 18th and 19th centuries. Noda makes use of both Russian and Qing archival documents as well as local Islamic sources. Through analysis of each party’s claims –mainly reflected in the Russian-Qing negotiations regarding Central Eurasia–, the book describes the role played by the Kazakh nomads in tying together the three regions of eastern Kazakh steppe, Western Siberia, and Xinjiang.